Influence of relaxation modes on membrane fouling in submerged membrane bioreactor for domestic wastewater treatment. (August 2017) - Habib, Rasikh; Asif, Muhammad Bilal; Iftekhar, Sidra; Khan, Zahiruddin; Gurung, Khum; Srivastava, Varsha; Sillanpää, Mika
Abstract: Relaxation and backwashing have become an integral part of membrane bioreactor (MBR) operations for fouling control. This study was carried out on real municipal wastewater to evaluate the influence of different operational strategies on membrane fouling at equivalent water yield. Four relaxation modes (MBR10+0, MBR10+1, MBR10+1.5 and MBR10+2 ) were tested to analyze membrane fouling behavior. For the optimization of relaxation modes, fouling rate in terms of trans-membrane pressure, hydraulic resistances and characteristics of fouling fractions were analyzed. It has been observed that cake layer resistance was minimum in MBR10+1.5 but pore blockage resistance was increased in all relaxation modes. Moreover, high instantaneous flux contributed significantly to fouling rate at the initial stage of MBR operations. Relaxation modes were also efficient in removing irreversible fouling to some extent. Under all relaxation modes, COD removal efficiency ranged from 92 to 96.5%. Ammonium and TP removal were on the lower side due to the short solids and hydraulic retention time. Graphical abstract: Highlights: Relaxation was effective for membrane fouling control. High instantaneous flux contributed significantly to fouling at initial stages. Relaxation modes were efficient in removing irreversible fouling to some extent. 10 min filtration and 1.5 min relaxation mode was the most efficient scenario. Similar characteristics of foulants on membrane surface and in bulk MBR.